Trust and Convenience Drive E-Money Adoption Among Students in Indonesia: Kepercayaan dan Kenyamanan Mendorong Adopsi E-Money di Kalangan Pelajar di Indonesia - Putra, Bisma Akbar Wahyu Tri; Sari, Herlinda Maya Kumala (Indonesian Journal of Law and Economics Review, 2024)
This study explores how perceived usefulness, convenience, service features, and trust influence Umsida students' decisions to use "DANA" e-money. A quantitative approach was employed, with data collected via questionnaires from 100 respondents using accidental sampling. Multiple linear regression analysis with IBM SPSS version 22 revealed that all four factors significantly affect the decision to use "DANA." The findings suggest that enhancing these aspects could increase e-money adoption among students, providing valuable insights for service providers. Highlight: Significant Influences: Usefulness, convenience, features, and trust impact e-money decisions. Quantitative Analysis: Data from 100 respondents analyzed using SPSS. Student Focus: Insights for boosting e-money adoption among Umsida students. Keyword: perceived usefulness, perceived convenience, service features, trust, e-money adoption